Global English: A Study of Factors Affect for English Language Learning Motivation in Sri Lankan Undergraduates - K.S.N., Prasangani (Elsevier Ltd., 2015)
he current study aimed to examine the factors affecting for English language learning motivation of undergraduates by utilizing Dornyei's (2009) L2 Motivational Self System. The study was conducted among 361 Sri Lankan undergraduates by using an adapted motivation questionnaire. Pearson correlation analysis was run to examine the relationships between the variables of ideal L2 self, ought to L2 self, motivated self, mastery goals, performance goals and social goals. The results of the study indicated the close link between social requirements of learning English and learner English learning self-concept. Further study validatedthe L2 motivational self system in Sri Lanka.